Advanced Processing of Food Waste Based Digestate for Mitigating Nitrogen Losses in a Winter Wheat Crop - Sánchez-Rodríguez, Antonio R.; Carswell, Alison M.; Shaw, Rory; Hunt, John; Saunders, Karen; Cotton, Joseph; Chadwick, Dave R.; Jones, Davey L.; Misselbrook, Tom H. (Frontiers in Sustainable Food Systems, 2018)
The anaerobic digestion of food waste converts waste products into “green” energy. Additionally, the secondary product from this process is a nutrient-rich digestate, which could provide a viable alternative to synthetically-produced fertilizers. However, like fertilizers, digestate applied to agricultural land can be susceptible to both ammonia (NH3) and nitrous oxide (N2O) losses, having negative environmental impacts, and reducing the amount of N available for crop uptake. Our main aim was to assess potential methods for mitigating N losses from digestate applied to a winter wheat crop and subsequent impact on yield. Plot experiments were conducted at two UK sites, England (North Wyke-NW) and Wales (Henfaes-HF), to assess NH3 and N2O losses, yield and N offtake following a single band-spread digestate application. Treatments examined were digestate (D), acidified-digestate (AD), digestate with the nitrification inhibitor DMPP (D+NI), AD with DMPP (AD+NI), and a zero-N control (C). Ammonium nitrate (NH4NO3) fertilizer N response plots (from 75 to 300 kg N ha−1) were included to compare yields with the organic N source. Across both sites, cumulative NH3-N losses were 27.6% from D and D+NI plots and 1.5% for AD and AD+NI of the total N applied, a significant reduction of 95% with acidification. Cumulative N2O losses varied between 0.13 and 0.35% of the total N applied and were reduced by 50% with the use of DMPP although the differences were not significant. Grain yields for the digestate treatments were 7.52–9.21 and 7.23–9.23 t DM ha−1 at HF and NW, respectively. Yields were greater from the plots receiving acidified-digestate relative to the non-acidified treatments but the differences were not significant. The yields obtained for the digestate treatments ranged between 84.2% (D+NI) and 103.6% (D) of the yields produced by the same N rate from an inorganic source at HF. Advanced processing of digestate reduced N losses providing an environmentally sound option for N management.